Alkali-Activation of Synthetic Aluminosilicate Glass With Basaltic Composition - Alzeer, Mohammad I. M.; Nguyen, Hoang; Cheeseman, Christopher; Kinnunen, Paivo (Frontiers in Chemistry, 2021)
Alkali-activated materials (AAMs) are a potential alternative to Portland cement because they can have high strength, good durability and low environmental impact. This paper reports on the structural and mechanical characteristics of aluminosilicate glass with basalt-like compositions, as a feedstock for AAMs. The alkali-activation kinetics, microstructure, and mechanical performance of the alkali activated glass were investigated. The results show that AAMs prepared from basalt glass have high compressive strength (reaching up to 90 MPa after 7 days of hydration) compared to those made using granulated blast furnace slag (GBFS). In addition, calorimetry data show that the hydrolysis of the developed glass and subsequent polymerization of the reaction product occur at a faster rate compared to GBFS. Furthermore, the obtained results show that the alkali activation of the developed glass formed sodium aluminosilicate hydrate (N-A-S-H) intermixed with Ca aluminosilicate hydrate gel (C-A-S-H), while the alkali activation of GBFS resulted in predominantly C-A-S-H gel. The developed glass can be formed from carbonate-free and abundant natural resources such as basalt rocks or mixtures of silicate minerals. Therefore, the glass reported herein has high potential as a new feedstock of AAMs.